2013
DOI: 10.1161/circulationaha.112.132159
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 1 Plays a Key Role in Diabetes Mellitus–Accelerated Atherosclerosis

Abstract: Background-In diabetes mellitus, vascular complications such as atherosclerosis are a major cause of death. The key underlying pathomechanisms are unclear. However, hyperglycemic oxidative stress derived from NADPH oxidase (Nox), the only known dedicated enzyme to generate reactive oxygen species appears to play a role. Here we identify the Nox1 isoform as playing a key and pharmacologically targetable role in the accelerated development of diabetic atherosclerosis. Methods and Results-Human aortic endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
327
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 334 publications
(342 citation statements)
references
References 52 publications
10
327
0
3
Order By: Relevance
“…In the vascular system, ROS regulate vasculogenesis, endothelial function, and vascular tone 3, 4. In cardiovascular diseases, such as hypertension,5 atherosclerosis,6 and pulmonary arterial hypertension,7 Nox‐derived ROS generation is increased, leading to endothelial dysfunction and vascular injury. The mammalian Nox family comprises 7 isoforms, Nox1 to 5 and dual oxidase 1 and dual oxidase 2, of which Nox1, 2, 4, and 5 have been identified in human vessels 8, 9.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the vascular system, ROS regulate vasculogenesis, endothelial function, and vascular tone 3, 4. In cardiovascular diseases, such as hypertension,5 atherosclerosis,6 and pulmonary arterial hypertension,7 Nox‐derived ROS generation is increased, leading to endothelial dysfunction and vascular injury. The mammalian Nox family comprises 7 isoforms, Nox1 to 5 and dual oxidase 1 and dual oxidase 2, of which Nox1, 2, 4, and 5 have been identified in human vessels 8, 9.…”
mentioning
confidence: 99%
“…Vascular Noxs have different functions in pathological conditions. Nox1 and Nox2 play a role in angiogenesis and atherosclerosis,3, 6 and Nox4 seems to be vasoprotective in ischemic and hypoxic conditions,10 but injurious in diabetes mellitus, where it promotes vascular fibrosis, diabetic nephropathy, and intravitreal neovascularization 11. Although Nox5 is expressed in mammalian vessels,12, 13, 14 there is a paucity of information on its role and biological significance in the cardiovascular system.…”
mentioning
confidence: 99%
“…NOX1 and NOX4 are expressed in the walls of the vasculature, whilst NOX2 and NOX4 are present in endothelial cells 34. In separate studies using a mouse model, genetic deletion of NOX1 led to a decrease in atherosclerosis development using either an atherogenic diet (to induce T2D) or streptozotocin (STZ) (to induce T1D) 9. Deletion of NOX2 has no effect on lesion development in the aortic sinus, but reduced lesion size in the descending aorta 35.…”
Section: Diabetes and Cardiovascular Diseasementioning
confidence: 99%
“…The Brownlee hypothesis is an area of ongoing controversy and active investigation. A recent study has suggested that this excess of mitochondrial ROS may not be a universal finding [14], and there is increasing evidence of the importance of nonmitochondrial sources of ROS, including cytosolic production of ROS by NADPH oxidase [15]. Furthermore, although the polyol pathway has now been under active investigation for over 40 years, except for some limited data in neuropathy, agents that inhibit this pathway, such as aldose reductase inhibitors, have not been widely used in clinical practice.…”
Section: Mechanisms Of Complications: the Current Paradigmmentioning
confidence: 99%